Comprobación experimental de la tecnología del sistema intensivo de cultivar arroz SRI en la zona de la Cuca provincia de El Oro - Cruz Alomaliza, Gabriel Vicente (2008)
The present work of investigation experimental Confirmation of the technology of the intensive system of rice cultivation "SRI" for the rice in the area of La Cuca, county of El Oro; it was carried out in the canton Arenillas during the year 2007 and consisted on to observe and to measure the development of three varieties of rice; Iniap-14, IR-43 and Fedearroz-50 in the system SRI, in comparison with the traditional one, in two seeding distances. The objectives were: 1. To establish the advantages of the new intensive technology of the cultivation of the rice SRI; 2. To determine the best seeding distance with three varieties of rice under the traditional system and SRI; and, 3. To carry out an economic analysis of each treatment. The 12 combinations were assigned at random and according to the transplant system; with four replications each one, totalling 48 experimental units. The statistical analyses were highly significant for the varieties in what corresponded to vegetative cycle, plant height, panicles longitude, grains per panicle, percentage of vain grain and relationship grain-straw. Likewise for distances in number of macollos/planta, panicles number, panicles longitude, relationship grain-straw and yield. In systems they were significant for vegetative cycle, plant height, number of macollos/planta, grain-vain percentage, relationship grain-straw. The most precocious system was the SRI, and the variety INIAP-14 resulted to be the most premature in comparison to the other ones; the IR-43 presented higher number of macollos, the same as the Traditional system; the Fedearroz-50 reached the higher grain/panicle production. In yield the SRI resulted to be better than the Traditional one. The variety Fedearroz-50 and the system SRI obtained an economic benefit of $2 100, with a production of 7,9 t/ha equivalent to 106 qq whose sale price was of $26,00 per unit. In the Traditional system, the variety Fedearroz-50, had an economic benefit of $2 041, obtaining a production of 7,9 t/ha equivalent to 106 qq, with a sale price to the public of $26,00.